Group stereotypes and symbols of overcoming difficult social situations in the image of small groups - Olha Pletka (Mental Health: Global Challenges Journal, 2019)
Introduction. Sometimes a person meets with complex social situations. How a person lives these situations down? What is the experience that supports and drives a person to recovery? How does the group help for a person in this? These questions now arise for each of us, because there is no person in the world who would have had the experience of living in complex social situations